Amen, I Say to You He Will Surely Not Lose His Reward (Mt 10:42): A LOOK AT THE “REWARD” AND ITS FILIPINO CONTEXT - Natividad, Maria Lucia C. (Asian Horizons, 2014)
Grace is God’s Self-gift through Christ in the Spirit and the acceptance of this divine gift. The reward is the participation in the creative and transforming love of God for all. It is a sharing in God’s divine life now and for all eternity. Reward is the depth meaning of human life expressed in the love for God and neighbour and the ultimate reward is the abundant life in the heavenly kingdom. An understanding of the term “reward” is realized by looking at the usage of this term particularly in Matthew’s gospel, the Church teaching’s definition and explanation of “reward” and its practical understanding in the faith-life experiences of the Filipino Catholics.